Pentingnya Pengungkapan (Disclosure) Laporan Keuangan Dalam Meminimalisasi Asimetri Informasi: Kajian Literatur dan Riview Beberapa Artikel Penelitian Terkait Pengungkapan - Ery Hidayanti; Sunyoto Sunyoto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2012)
Agency theory arising due to the different interests between managers as agents of the owners of capital as a principal. This problem arises from the desire berrnula the agency for not acting in the best interests principal Jensen and Meckling (1976). The agent to make a more informed decision to maximize their own welfare than the welfare principal. This is where the asymmetry arises, as principal on the other hand is in need of all the relevant information about the overall condition of the company, but not rnempunyai access to internal corporate information, but the information is very useful for making economic decisions. Based on this phenomenon arising from the lack of transparency in the financial statements of the agent causing the authors formulate the problem associated with pendisclosuran purposes, gains and losses as well as the relationship between pendisclosuran pendisclosuran against asymmetry. Thus the aim of this paper is to describe the importance of disclosure to the financial statements in order to overcome or minimize the information asymmetry through the publication of financial statements. Hopefully with a full disclosure by firms all relevant financial information will ultimately be very useful for stakeholders and will reduce the asymmetry of information that has been happening.